Effects of Monolaurin on Oral Microbe–Host Transcriptome and Metabolome - Silva, Viviam de Oliveira; Pereira, Luciano José; Pasetto, Silvana; da Silva, Maike Paulino; Meyers, Jered Cope; Murata, Ramiro Mendonça (Frontiers in Microbiology, 2018)
This in vitro study aimed to evaluate Monolaurin effects against Aggregatibacter actinomycetemcomitans (Aa) and determine their effects on the host transcriptome and metabolome, using an oral cell / bacteria co-culture dual-chamber model to mimic the human periodontium. For this, was used a monolayer of epithelial keratinocytes (OBA-9) and a subepithelial layer of fibroblasts (HGF-1). The invasive periodontopathogen Aa was applied to migrate through the cell layers. The Monolaurin treatments (25 µM or 50 µM) were added immediately after the inoculation of the dual-chamber model with Aa. The time of exposure of the microorganism to treatment was 24 hours. Transcriptional factors and metabolites produced were quantified in the remaining cells layer (insert end basal chamber) and on supernatant released from the cells. The genes IL-1-α, IL-6, IL-18 and TNF analyzed in HGF-1 showed a decrease expression when treated with 25 µM or 50 µM of Monolaurin. In keratinocytes, the genes IL-6, IL-18 and TNF presented a higher expression when treated with 25 µM or 50 µM of Monolaurin. IL-1-α gene expression decreased in the group treated with 25 µM and 50 µM Monolaurin. The production of glycerol and pyruvic acid increased with 25 µM or 50 µM of Monolaurin. The 2-deoxytetronic acid NIST, 4-aminobutyric acid, glyceric acid and pinitol presented lower concentrations because of the treatment with 25 µM and/or 50 µM of Monolaurin. Use of monolaurin modulated the immune response and metabolite production when administered for 24 h in a dual-chamber model inoculated with Aggregatibacter actinomycetemcomitans.